Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpsyg.2020.609885
|View full text |Cite
|
Sign up to set email alerts
|

Coming Out to Parents in Lesbian and Bisexual Women: The Role of Internalized Sexual Stigma and Positive LB Identity

Abstract: The experience of “coming out” (CO) to parents is often a crucial event in the lives of lesbian and bisexual (LB) women, associated with lower internalized sexual stigma (ISS) and higher positive LB identity. Few studies have compared the experiences of LB women in the CO process. Rather, most prior research has either: (1) not addressed bisexuality or eliminated bisexual individuals from the analysis; (2) combined bisexual women and bisexual men in the same sexual orientation group; or (3) examined bisexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 82 publications
0
8
0
6
Order By: Relevance
“…These attitudes influence a higher level of internalized homonegativity, resulting in less acceptance of their bi identity [58]. Higher levels of positive identity in gay people have been previously highlighted in comparison to their bisexual peers [59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 96%
“…These attitudes influence a higher level of internalized homonegativity, resulting in less acceptance of their bi identity [58]. Higher levels of positive identity in gay people have been previously highlighted in comparison to their bisexual peers [59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 96%
“…The minority stress model documented that discrimination, stigma, violence, and social rejection could increase heightened stress levels and ultimately lead to risky health behaviors among sexual minorities [13]. Studies have also shown that bisexual individuals lacked social support from the minority community [38,39]. Future studies, including qualitative studies, could address the unique challenges of bisexual females.…”
Section: Discussionmentioning
confidence: 99%
“…First, we predicted that the German-version of the LGB-PIM would show acceptable model fit (Hypothesis 1). Second, we predicted positive associations between the five positive minority identity aspects (i.e., self-awareness, authenticity, community, intimacy, social justice) in people with diverse sexual orientations and their self-reported relationship quality, after controlling for relevant confounds, namely age (Baiocco et al, 2020;Bühler et al, 2021), gender identity (Marshall et al, 2020;Sommantico et al, 2019Sommantico et al, , 2020Song et al, 2021), sexual orientation (or couple gender in a sensitivity analysis; Baiocco et al, 2020;Morandini et al, 2018), relationship length (Bühler et al, 2021), and psychological distress (Braithwaite & Holt-Lunstad, 2017;Riggle et al, 2014;Hypothesis 2).…”
Section: The Present Studymentioning
confidence: 92%